India, the Indo-Pacific and the Quad - Roy-Choudhury, R; Sullivan De Estrada, K (Routledge, 2018)
Bound by the strategic primacy of the Indian Ocean and by the constraints on its sea-power projection, India's interests sit uneasily with those of the other Quad powers.